1987
DOI: 10.1017/s0021859600064212
|View full text |Cite
|
Sign up to set email alerts
|

Breed and sex effects on the development, distribution of muscle, fat and bone, and the partition of fat in pigs

Abstract: Dissection data from 341 carcasses collected over a period of 7 years at the Institute of Food Research, Bristol (Large White, 138 entire males and 112 females; Pietrain, 41 entire males and 31 females; Iron Age (European Wild Pig x Tamworth), 8 entire males and 11 females) were used to examine the growth of muscle, fat and bone in joints relative to the corresponding total tissue in the side, and the growth of the fat depots relative to total side fat.The musculature of Iron Age pigs was early maturing, as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
2
8
2
2
Order By: Relevance
“…Variation in fat depth response between sites after selection at a single site would have been expected in the S line of thẽ . Sex differences in fat depth at the shoulder, mid back and loin sites of measurement are consistent with the finding that the male pig deposits a greater proportion of its subcutaneous fat in the shoulder, neck and fore parts than the female (Fortin et al 1987). It is difficult to explain, other than by chance, the similarity of the sexes in K fat depth found in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Variation in fat depth response between sites after selection at a single site would have been expected in the S line of thẽ . Sex differences in fat depth at the shoulder, mid back and loin sites of measurement are consistent with the finding that the male pig deposits a greater proportion of its subcutaneous fat in the shoulder, neck and fore parts than the female (Fortin et al 1987). It is difficult to explain, other than by chance, the similarity of the sexes in K fat depth found in this study.…”
Section: Discussionsupporting
confidence: 82%
“…This explains why heavy carcasses from Duroc and Lacombe pigs showed a decrease in lean content and an increase in the relative contribution of fat depots compared with light carcasses from the same breed. At the same time, Fortin et al (1987) reported that higher relative deposition rate for subcutaneous fat was an indication of earlier maturity. The Iberian breed is known for its early maturing fat deposition (Daza et al 2006), explaining the high-fat content in Iberian carcasses and why no differences were observed between slaughter weights.…”
Section: Discussionmentioning
confidence: 95%
“…Allometric function explains that fat is a late maturing tissue (Fortin et al 1987) and usually develops faster when animals are closer to maturity. This explains why heavy carcasses from Duroc and Lacombe pigs showed a decrease in lean content and an increase in the relative contribution of fat depots compared with light carcasses from the same breed.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have pointed to differing muscle composition between the sexes. Fortin et al (1987) documented that in comparison with gilts, boars have heavier neck and chest muscles and lighter pelvic and limb muscles. Similar results were found as regards carcass hind legs and shoulders, wherein boars showed the lowest proportion among all pig groups.…”
Section: Resultsmentioning
confidence: 99%